Market models and higher education in the 21st century. In pursuit of internationalization, understandings of a singularity - García León, Leonel; Arciga Zavala, Blanca Estela (Emerging Trends in Education, 2023)
The perspective on the market for higher education is essential in the understanding of the paths for the internationalization, that mainly our institutions are in pursue to increase their prestige and achievable economic resources. Nonetheless, reflection is needed in regard the application of market models, institutional diversity, institutional profiles and the feasibility of the double degrees and joint-degree programs. Lead us to the understanding of the junctions and paradoxes that Latin-American public institutions in their quest for upholding the equilibrium between social responsibility and self-interest, to provide identity to the “good institution” in the so-called global era. To this end, an analytical strategy of key texts and documents on market theories and models and higher education was adopted.Keywords: higher education; market models; internationalization; dual degrees; joint programs.